(untitled) (JOSAR (Journal of Students Academic Research), 2021)
Accidents often occur suddenly and are not planned, which can result in injury. If an accident occurs, first aid must be carried out immediately before being given further assistance. The Indonesian Red Cross (PMI) is one of the institutions in Indonesia engaged in the health sector that can provide first aid in the event of an accident. However, often when an accident occurs, the victim is not immediately given help due to lack of information to the public. In this study, the authors made an application of the Certainty Factor method so that the public could recognize and know what to do with victims who had an injury or accident. This application is made to present the knowledge of an expert in approaching a problem, which is called an expert system. This expert system will display symptoms that can be selected according to the symptoms felt by the victim. The final results of this application obtained a value of 78% from the calculation using the Certainty factor method in bleeding diseases. From the tests carried out, it shows the beta test results obtained by a value of 58.25% indicating that the respondents strongly agree with the usefulness of the application system